Analisis Komparasi antara Model Concern for Information Privacy dan Model Internet User's Information Privacy Concern: Konsekuensi untuk Proses Penyelarasan Managemen Database (Studi Empiris di Jogyakarta) - Sumiyana Sumiyana (The Indonesian Journal of Accounting Research, 2013)
This research compares two models in information privacy domain. The research intends to find a refined model for behavioral dimensions of database management systems. The first model is Concern for Information Privacy (CFIP) and the second one Internet Users Information Privacy Concern (IUIPC). The research finds that both models do not fit for Indonesian users. This study finds empirical evidence that CFIP has medium-fit level and IUIPC has lower-fit level. Therefore, this study concludes that IT managers should be concerned with the relevant dimensions. Consequently, this research provides a new model that is more suitable for Indonesian users. The new model combines the two models and eliminates the irrelevant dimensions. The new model suggests that two out of five dimensions affect behavioural intention. It means that Indonesian users prefer to present their personal information privacy without considering control and anxiety. In addition, the study does not find that trusting belief mediate nor intervene the direct relationship between personal information privacy and the behavioural intentions. Finally, this research infers that contingent situations of Indonesian users have consequences on the alignment process of database management in the Indonesian firms.